Penerapan media quizizz untuk meningkatkan hasil belajar siswa pelajaran tematik siswa kelas IV SD Bukit Aksara Semarang - Hendro Utomo (Perkumpulan Kualitama Edukatika Indonesia, 2020)
Classroom action research has been carried out to improve and improve student learning outcomes through classroom action research using Quizizz media. This research was conducted in class IV SD Bukit Aksara Semarang for the 2020/2021 school year, with 37 students. This study aims to determine whether learning using Quizizz media can improve student learning outcomes and learning activities. The focus of this research is thematic learning outcomes which include cognitive, affective, psychomotor aspects, as well as student learning activities and science process skills, as well as teacher performance. The results of this study indicate that the activity from the initial conditions, cycle 1, and cycle 2 continues to increase. In the initial conditions to cycle 1 and to cycle 2 the percentage of students whose activeness was in the low category continued to decline, namely 70% - 18.33% - 6.67%. Medium category is from 20% - 56.67% - 50%. While the high category is from 10% - 25% - 43.33%. It can be concluded that thematic learning through Quizizz media can improve student learning outcomes and learning activities.